Association of the caprine calpastatin MspI polymorphism with growth and reproduction traits in Saanen goats - ARDICLI, S; USTUNER, H; ARSLAN, O (Journal of the Hellenic Veterinary Medical Society, 2021)
This study was designed to evaluate the effects of calpastatin (CAST) MspI polymorphism on some growth and reproduction traits, including birth weight, first breeding weight, litter size, and average daily weight gain in Saanen goats. In this sense, blood samples obtained from 73 purebred female Saanen goats were used for genotyping. Genomic DNA was isolated by the phenol-chloroform method and used to determine CAST genotypes, including MM, MN, and NN, by means of the PCR-RFLP method. The population genetic parameters were estimated based on allelic distribution and the data were statistically analysed using analysis of variance (ANOVA) using a general linear model (GLM). Results revealed that N allele frequency was remarkably high (0.64) and the MM genotype was not present. The frequency of the heterozygous genotype was 59.62%. Concerning ANOVA results, significant differences were found between genotypes of the CAST locus concerning birth weight (P<0.05). In this respect, animals with the NN genotype were associated with higher birth weight means (2.85±0.29 kg) compared to heterozygous animals (2.53±0.24 kg). There was no significant association between the CAST marker and any of the remaining phenotypic traits evaluated. The present results suggest that focusing on this genomic region may be particularly useful in improving birth weight in goats which can be considered as an early indicator of post-weaning animal growth and survival.